2018
DOI: 10.15761/jcmm.1000103
|View full text |Cite
|
Sign up to set email alerts
|

Molecular study of colistin resistant clinical isolates of Enterobacteriaceae species

Abstract: Background: There is recent concern about the development of colistin resistance that may disturb the antibiotics therapy used for extended beta lactamase producing Enterobacteriaceae species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…This result indicates that many significant Gram-negative isolates pose mechanism for colistin resistance. Various other authors have also reported colistin resistance among a variety of Gram-negative isolates including Acinetobacter and Pseudomonas [17], E. coli, K. oxytoca, K. pneumoniae, Acinetobacter iwoffii, E. agglomerans, Enterobacter cloacae, P. putida, and Pseudomonas aeruginosa [18], Klebsiella, E. coli, Enterobacter, and Acinetobacter [19], and Klebsiella [20]. Many colistin-resistant clinical isolates were resistant to a wide variety of antimicrobial agents, including penicillins, cephalosporins, monobactams, carbapenems, aminoglycosides, quinolones, nitrofurans, etc.…”
Section: Discussionmentioning
confidence: 88%
“…This result indicates that many significant Gram-negative isolates pose mechanism for colistin resistance. Various other authors have also reported colistin resistance among a variety of Gram-negative isolates including Acinetobacter and Pseudomonas [17], E. coli, K. oxytoca, K. pneumoniae, Acinetobacter iwoffii, E. agglomerans, Enterobacter cloacae, P. putida, and Pseudomonas aeruginosa [18], Klebsiella, E. coli, Enterobacter, and Acinetobacter [19], and Klebsiella [20]. Many colistin-resistant clinical isolates were resistant to a wide variety of antimicrobial agents, including penicillins, cephalosporins, monobactams, carbapenems, aminoglycosides, quinolones, nitrofurans, etc.…”
Section: Discussionmentioning
confidence: 88%
“…Studies from North Africa also reported humans as reservoir for COL-resistant organisms [ 28 , 60 , 76 , 77 , 89 97 ]. In Egypt, 20 strains (six E .…”
Section: Plasmid-mediated Colistin Resistance Among Isolates From mentioning
confidence: 99%
“…coli , nine Pseudomonas aeruginosa , three K . pneumoniae , and two Acinetobacter baumannii ) carrying mcr -1 and one tigecyline-resistant Enterobacter hormaechei (isolated during 2015) carrying mcr -9 on IncHI2 plasmid were detected among 285 clinical MDR isolates (7%) from individuals [ 89 95 ], suggesting low circulation of mcr genes among Enterobacteriaceae and non- Enterobacteriaceae causing difficult-to-treat diseases in Egypt, and that organisms producing MCR-9 had been present in North Africa, since at least half a decade. It also suggested that organisms in the ESKAPE ( Enterococcus , Staphylococcus , K .…”
Section: Plasmid-mediated Colistin Resistance Among Isolates From mentioning
confidence: 99%
See 1 more Smart Citation
“…Colistin-resistant Pseudomonas aeruginosa (CRPA) strains have been detected in many infections, including wound and bloodstream. (Lee and Ko 2014;El Sayed Zaki et al 2018;Osei Sekyere 2019). Resistance to polymyxins most frequently results from the modification of the LPS caused by the addition of a 4-amino-4-deoxy-l-arabinose moiety in the lipid A structure and the underlying mutations are frequently tracked to the PmrAB or PhoPQ twocomponent regulators, which in turn lead to the activation of the pmrACADTEF operon (Osei Sekyere et al 2016;Chalmers et al 2018).…”
Section: Introductionmentioning
confidence: 99%